A Comparative study between intravenous Lignocaine infusion and ultrasound guided Transversus abdominis plane block plus rectus sheath block for intraoperative hemodynamic stability in laparoscopic cholecystectomy surgery - Hemalatha, Vemuri; vadlamudi, Venkateswara rao; Vijaya, Sammana; teja reddy, Avula Charan; Chaithanya, K. Krishna (Journal of Neonatal Surgery, 2025)
Introduction: Laparoscopic cholecystectomy surgery is currently the mainstay surgical procedure for the treatment of cholelithiasis and intraoperative and postoperative analgesia is still dominated by opioids. However, postoperative complications can easily occur. This study focused on the hemodynamic variations and analgesic effects between the two methods in patients undergoing laparoscopic cholecystectomy by intravenous infusion of lignocaine and ultrasound-guided transverse abdominis plane block plus rectus sheath block, providing new ideas for multimodal analgesic strategies and improvements of the quality of postoperative recovery in patients. Methods: This is an observational study conducted after ethical committee approval. In this study, 60 patients were allocated into 2 groups to receive intravenous Lignocaine infusion (group L) and transversus abdominis plane block plus rectus sheath block (group B). Hemodynamic variations during intraoperative period were monitored and post operative analgesia and bowel recovery were assessed. Results: Intravenous Lignocaine infusion shows significant intraoperative hemodynamic stability (p value -0.025) and postoperative bowel recovery (p valve-0.0001) and block shows significant VAS scores (p value -<0.0001) Conclusion: intravenous lignocaine infusion provided better hemodynamic stability intraoperatively and faster bowel recovery whereas transversus abdominis plane plus rectus sheath block provided better postoperative analgesia